2015
DOI: 10.1182/blood-2015-04-640037
|View full text |Cite
|
Sign up to set email alerts
|

Modulating platelet reactivity through control of RGS18 availability

Abstract: Key Points• RGS18 acts as a brake on persistent or inappropriate platelet activation after it is released from binding sites in resting platelets.• Control of free RGS18 levels provides a mechanism for coordinating signaling networks in platelets.Most platelet agonists activate platelets by binding to G-protein-coupled receptors. We have shown previously that a critical node in the G-protein signaling network in platelets is formed by a scaffold protein, spinophilin (SPL), the tyrosine phosphatase, Src homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
(77 reference statements)
4
19
0
Order By: Relevance
“…Consistently, it was previously shown that knockdown of RGS18[24,25], RGS10[26] or mutation of the RGS binding site on Gαi[27] results in increased platelet reactivity. At this ISTH conference, Gupta et al confirmed that knockdown of RGS10 results in a gain of platelet function, in particular in response to stimulation by the second wave mediators, ADP and TxA 2 [28].…”
Section: Classical Hemostasis – Balancing Platelet Adhesiveness In CIsupporting
confidence: 77%
“…Consistently, it was previously shown that knockdown of RGS18[24,25], RGS10[26] or mutation of the RGS binding site on Gαi[27] results in increased platelet reactivity. At this ISTH conference, Gupta et al confirmed that knockdown of RGS10 results in a gain of platelet function, in particular in response to stimulation by the second wave mediators, ADP and TxA 2 [28].…”
Section: Classical Hemostasis – Balancing Platelet Adhesiveness In CIsupporting
confidence: 77%
“…26 As an example of pathway convergence, dissociation of the SPL/RGS complex also occurs when endothelium-derived PGI 2 suppresses platelet activation by raising platelet cAMP levels ( Figure 2). 31 For Rap1b, regulation occurs at the level of Rasa3, whose ability to act as a GAP is inhibited by signaling downstream of G i2 . 25,32 Rap1b 33 and CalDAG-GEF1, 34,35 like spinophilin, are targets for cAMP-dependent phosphorylation.…”
Section: The Platelet Signaling Network Is An Integrating Enginementioning
confidence: 99%
“…RGS18 negatively modulates the function of G-protein-coupled receptors (GPCRs). RGS18 makes platelets less sensitive to activation (30,31). Since PLD2 can be activated downstream of GPCRs (32), it is conceivable that the increase in RGS18 is a compensatory response to some of the effects of PLD2 overexpression.…”
Section: Localization Of Wnt1-inducible Signaling Pathway Protein 1mentioning
confidence: 99%